Conciencia fonológica y su impacto en el desarrollo del lenguaje en los niños de 4 años de educación inicial de la Escuela 20 de Enero - Cruz Carriel, Damaris Gabriela (2023)
The case study was carried out at the 20 de Enero School, with the objective of determining phonological awareness and its impact on language development in 4-year- old children of Initial Education. The applied methodology consisted of a non- experimental design, quantitative field and documentary research approach; In addition to the interview technique and direct observation with their respective instruments, which were directed to a sample of 34 infants and 2 teachers. The results were: one of the teachers does not have clear knowledge about what phonological awareness consists of. There is no formal planning of activities or strategies where each of the actions that promote the child's phonological awareness are established, since the most used activity is children's songs or rhymes. Most children were able to reproduce vowel sounds, separate the sounds of a word into two or three phonemes, but not accurately, and recall familiar words. In conclusion, phonological awareness is an essential skill in the language development of children in the initial stage of their education because it allows them to recognize and manipulate the individual sounds that make up words, such as syllables and phonemes. Phonological awareness encourages proper pronunciation and listening comprehension, thus contributing to the comprehensive development of language and communication in preschool children.